COMMUNITY PARTICIPATION IN COVERING THE BEACH ABRASION IN NAGARI MANGGOPOH PALAK GADANG, DISTRICT OF TAPAKIS - Hakiki Mulyani; Helfia Edial (JURNAL BUANA, 2019)
Abstrack This study aims to 1) find out the role of the community in overcoming abrasion on the coast of Ulakan Nagari Manggopoh Palak Gadang, 2) knowing the creation of abrasion emergency dikes made by the community. This study uses a quantitative descriptive approach. Analysis techniques using percentages are collected through data collection techniques through observation, interviews, documentation and questionnaires. The population of 915KK and the 46KK sample taken by random sampling was 5%. The results of this study are 1) Community participation in overcoming abrasion on the Ulakan coast is relatively moderate, only 52%. 2) Community participation in the making of abrasion emergency dikes by the community on the Ulakan coast is relatively moderate, at only 46%.